2017
DOI: 10.9787/pbb.2017.5.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Classification of the AP2/EREBP Gene Family in the Cucurbitaceae Species

Abstract: This is an Open-Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/4.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited. ABSTRACT AP2/EREBP gene family consists of transcription factor genes with a conserved AP2 DNA-binding domain and is involved in various biological processes. AP2/EREBP gene families were identified through gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The AP2/ERF superfamily is one of the largest TF families in the plant kingdom, and it has been successfully identified and investigated in many plant species of sequenced genomes [ 35 37 ]. Although the AP2/ERF superfamily in peppers was reported by Jin et al [ 38 ], they indicated that CaAP2/ERFs might be involved in the response to P. capsici in peppers.…”
Section: Discussionmentioning
confidence: 99%
“…The AP2/ERF superfamily is one of the largest TF families in the plant kingdom, and it has been successfully identified and investigated in many plant species of sequenced genomes [ 35 37 ]. Although the AP2/ERF superfamily in peppers was reported by Jin et al [ 38 ], they indicated that CaAP2/ERFs might be involved in the response to P. capsici in peppers.…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptome data has also enabled genome-wide studies of individual salt responsive genes as well as their functions. For example, Kumar et al [ 21 ] reported that the ectopic expression of OsSta2 gene in rice enhanced salt tolerance, while AP2/EREBP and dehydrin genes have been characterized in Cucurbitaceae species [ 22 , 23 ]. Also, the transcriptome of plants growing under other abiotic stresses such as cold [ 24 , 25 ], drought [ 26 , 27 , 28 , 29 ], and heat [ 30 ] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The AP2/ERF superfamily is one of the largest TF families in the plant kingdom, and it has been successfully identi ed and investigated in many plant species of sequenced genomes [47][48][49]. Although the AP2/ERF superfamily in peppers was reported by Jin et al [50], they indicated that CaAP2/ERFs might be involved in the response to P. capsici in peppers.…”
Section: Discussionmentioning
confidence: 99%